2020
DOI: 10.1371/journal.pone.0231537
|View full text |Cite
|
Sign up to set email alerts
|

Clustered micronodules as predominant manifestation on CT: A sign of active but indolently evolving pulmonary tuberculosis

Abstract: To investigate the prevalence, patient characteristics, and natural history of clustered micronodules (CMs) in active pulmonary tuberculosis. Materials and methods From January 2013 through July 2018, 833 consecutive patients with bacteriologically or polymerase chain reaction-proven active pulmonary tuberculosis were retrospectively evaluated. CMs were defined as a localized aggregation of multiple dense discrete micronodules, which primarily distributed around small airways distal to the level of the segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…7 ). Furthermore, lung biopsies in patients with early stage TB showing clusters of micronodules on CT and whose acid-fast bacilli (AFB) smear test and PCR assay were negative, demonstrated peribronchiolar granulomas [ 26 ]. Some granulomas were confined to the peribronchiolar interstitium with no caseation necrosis or invasion of the airway or alveolar space.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…7 ). Furthermore, lung biopsies in patients with early stage TB showing clusters of micronodules on CT and whose acid-fast bacilli (AFB) smear test and PCR assay were negative, demonstrated peribronchiolar granulomas [ 26 ]. Some granulomas were confined to the peribronchiolar interstitium with no caseation necrosis or invasion of the airway or alveolar space.…”
Section: Introductionmentioning
confidence: 99%
“…Both GS and CS seem to be post-primary in immunocompetent individuals and were described as associated with perilymphatic-predominant nodularity rather than centrilobular-predominant nodularity [ 13 ]. A recent study showed the time interval for minimal radiologic progression of these lesions was greater than 6 months and their extent increased with disease progression, frequently accompanied by a pattern of bronchogenic spread and consolidation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Computed tomography (CT) is a more widely available imaging tool in TB-endemic regions of the world. Certain features on CT, including lung consolidation, lung nodules in the typical tree-in-bud pattern, pleural effusion, and others, are known to suggest active PTB ( 14 16 ). Determining the strength of the association between these CT features suggestive of active TB and the RMA on FDG PET is crucial for guiding the application of CT, a more widely available imaging technique, for treatment response assessment of patients treated for PTB.…”
Section: Introductionmentioning
confidence: 99%